PENGARUH POWER OTOT TUNGKAI DAN FLEKSIBILITAS PINGGANG TERHADAP KEMAMPUAN TENDANGAN SABIT - Muhammad Rinaldi; Dadan Muldan (Journal of Physical Education and Sport Science, 2022)
The Effect of Leg Power and Waist Flexibility on Sickle Kick Ability at the Tread Suci PIMDA 143 Kuningan Training Center". The aims of the study were (1) to determine the effect of leg power on the sickle kick ability at the Tapak Suci PIMDA 143 Kuningan Regional Training Center (2) to determine the effect of waist flexibility on the sickle kick ability at the Tapak Suci PIMDA 143 Kuningan Training Center. This study uses a quasi-experimental method with quantitative research, the benefits of this theory are useful for clarifying a theory. The population of all athletes from the Pelatda Tapak Suci PIMDA 143 Kuningan, totaling 20 athletes. And the sample uses a porposive sampling technique, which is also all athletes from the Pelatda Tapak Suci PIMDA 143 Kuningan, totaling 12 athletes. This study aims to determine the relationship between leg power and hip flexibility on the ability to kick the sickle at the Tapak Suci PIMDA 143 Kuningan Regional Training Center.